Can We Pharmacologically Target Dishevelled: The Key Signal Transducer in the Wnt Pathways? - Micka, Miroslav; Bryja, Vítězslav (Handbook of experimental pharmacology, 2021)
Dishevelled (DVL) is the central signal transducer in both Wnt/β-catenin-dependent and independent signalling pathways. DVL is required to connect receptor complexes and downstream effectors. Since proximal Wnt pathway components and DVL itself are upregulated in many types of cancer, DVL represents an attractive therapeutic target in the Wnt-addicted cancers and other disorders caused by aberrant Wnt signalling. Here, we discuss progress in several approaches for the modulation of DVL function and hence inhibition of the Wnt signalling. Namely, we sum up the potential of modulation of enzymes that control post-translational modification of DVL - such as inhibition of DVL kinases or promotion of DVL ubiquitination and degradation. In addition, we discuss research directions that can take advantage of direct interaction with the protein domains essential for DVL function: the inhibition of DIX- and DEP-domain mediated polymerization and interaction of DVL PDZ domain with its ligands.
Keywords: Wnt Signaling Pathway; Phosphoproteins; Casein kinase 1; Humans; Dishevelled; Dishevelled Proteins; protein dishevelled; DIX oligomerization; lidé; PDZ inhibitors; Wnt signalling-related diseases; fosfoproteiny; Adaptor Proteins, Signal Transducing; adaptorové proteiny signální transdukční; signální dráha Wnt